Development of operator-oriented peer-to-peer energy trading model for integration into the existing distribution system - Heo, Kangjoon; Kong, Junhyuk; Oh, Seongmun; Jung, Jaesung (International Journal of Electrical Power and Energy Systems, 2021)
Recently, peer-to-peer (P2P) energy trading has attracted considerable attention as an approach to overcome current challenges faced by the dissemination policy of each country for renewables-based distributed energy resources. However, existing trading models do not provide solutions for the receptivity problem in trading from the perspectives of customers and related organizations. In this regard, this paper proposes a novel P2P energy trading model that can be integrated into the existing distribution system. An operator-oriented trading scheme is developed to lower barriers to allow entry into P2P trading. The operator, instead of each participant, decides the marginal/trading price and trading schedules. Unlike in the existing model, the marginal price that accommodates various electric tariffs and sales systems is derived to obtain high receptivity from customers. Furthermore, service charges comprising charges for network usage and platform service are determined to develop a feasible trading model. The proposed model achieves acceptance from the utility company and platform operator in terms of service charges. Further, a matching algorithm is formulated considering derived elements; accordingly, a constrained optimization problem is formulated, and the Lagrange multiplier method is applied to create an optimal trading schedule that maximizes social welfare while preventing imbalance in revenues between buyers and sellers. The actual data for various types of loads and distributed energy resources are applied to the IEEE 18-bus distribution system to verify the performance of the proposed P2P trading scheme.
Keywords: Buyers and sellers; Constrained optimi-zation problems; Distributed Energy Resources; Distribution systems; Lagrange multiplier method; Matching algorithm; Terms of services; Utility companies; Matching algorithm; Operator-oriented trading; Peer-to-peer energy trading; Price determination; Price modulation; Service charge